Workshop Kewirausahaan Implementasi Sederhana Akuntansi dan Pengelolaan Keuangan bagi Wirausaha Pemula - Siska Priskilla; Muhammad Fathul Arifin; Yusri (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Accounting is an activity to calculate and account for something that has to do with the management of the financial sector of a company to its owner for the trust that has been given to the manager to carry out company activities, information systems that measure business activities, process data into reports and communicate the results to decision makers. . This is very important needed to measure our performance and targets whether they have been achieved or not. Many small businesses go bankrupt when in fact they have the potential to become big, just because of this financial record problem. The goal to be achieved through community service activities is to be able to understand well in managing independently related to business/business financial management properly. The method of implementing this activity is through training in providing practical and direct material and evaluation during the activity. The implementation of community service is carried out in one activity in the form of theoretical material and practical practice material on existing case studies, all participants are declared to have passed and were able to complete the case studies given by the speaker. Workshop activities are very useful for all people, especially young entrepreneurs who need to learn a lot about accounting in the hope that it can be carried out in a sustainable and coordinated manner.